Evaluation of the Quality of Government and the Delivery of Selected Public Goods in Poland on a Regional Level - Miłaszewicz, Danuta (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The possibilities of the development of regional economies and communities, as well as achieved standard of living, depends on the efficient operation and quality of regional institutions that exercise government authority. The aim of the article is to compare the quality of the government in the Polish regions (NUTS 2) and the spatial differentiation of access to basic public goods (education, health, security). The analysis of the quality of the government was based on the indicators of the quality of public institutions that exercise government authority in the regions of Europe. The study of accessibility to basic public goods in the Polish regions has been based on the key indicators characterizing the quantitative results of the implementation of public tasks in the field of education, health and security. The analysis shows that standards of living in the Polish regions vary not only because of disparities in GDP per capita and the supplied by the regional authorities amount of public goods, but also due to the significant differences in the quality of government in the regions.